La polis como articulación social: el caso arcadio - Cardete del Olmo, Mª Cruz (Gerión. Revista de Historia Antigua, 2005)
Because of the double romantic concept about Arcadia (on the one hand, the Arcadia felix; on the other hand, the rough Arcadia), the historiography has considered that the polis did not develop in Arcadia until the end of the VIth century and the Vth century. Hovewer, I think that there are enough evidences (city-ethnics, civic mints, interstate relations, Pythian and Olympic victories and relations, a delimited and structured territory and urban archaeological evidence) to say that from the 7th century there was a polis organization in Arcadia, as we can see in other Greek areas.